Predicting dengue outbreaks in Brazil with manifold learning on climate data. (15th April 2022) - Souza, Caio; Maia, Pedro; Stolerman, Lucas M.; Rolla, Vitor; Velho, Luiz
Abstract: Tropical countries face urgent public health challenges regarding epidemic control of Dengue. Since effective vector-control efforts depend on the timing in which public policies take place, there is an enormous demand for accurate prediction tools. In this work, we improve upon a recent approach of coarsely predicting outbreaks in Brazilian urban centers based solely on their yearly climate data. Our methodological advancements encompass a judicious choice of data pre-processing steps and usage of modern computational techniques from signal-processing and manifold learning. Altogether, our results improved earlier prediction accuracy scores from 0.72 to 0.80, solidifying manifold learning on climate data alone as a viable way to make (coarse) dengue outbreak prediction in large urban centers. Ultimately, this approach has the potential of radically simplifying the data required to do outbreak analysis, as municipalities with limited public health funds may not monitor a large number of features needed for more extensive machine learning approaches. Highlights: Dengue outbreak prediction using climate data. Signal processing and manifold learning for prediction problems. Improved earlier prediction accuracy scores from 0.72 to 0.80.